Multiple sclerosis and related disorders : clinical guide to diagnosis, medical management, and rehabilitation - Rae-Grant, Alexander; Fox, Robert, 1969-; Béthoux, François (Demos Medical, 2013)
Multiple Sclerosis and Related Disorders provides evidence-based data and experience-based guidance for delivering quality long-term care to MS patients. Information on disease history, pathophysiology, and biology is included to provide clinicians with a framework for understanding current diagnosis, monitoring, and treatment strategies for these disorders. In addition to thoroughly reviewing the newest disease-modifying treatments, the authors have devoted significant focus to the symptoms that frequently manifest and their treatment options. Symptoms and functional limitations are the ""fac